El movimiento de teatro independiente latinoamericano: origen, transiciones y pervivencia - Cedeño Méndez, Rosanna (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
Independent theater in Latin America had its genesis in 1930 when Leónidas Barletta founded El Teatro del Pueblo in the city of Buenos Aires, a project characterized by its social, ethical and political dimension, inaugurating a movement that gradually spread from the capital of Buenos Aires to the rest of Latin America, seeking to challenge the theatrical status quo, both commercial and official, to make room for a modern and popular theater. Then, in the sixties and seventies, already as a continental phenomenon, the independent movement transcended as the most important space for stage experimentation and renewal of theatrical and poetic languages, guided by an emancipatory vocation of social and political tone that the community adopted as a form of organization and creation, and mainly, where it sought to forge a Latin American theatrical identity. The main objective of this research has been to examine this movement through three companies: El Galpón from Uruguay, La Candelaria from Colombia and Yuyachkani from Peru, to reconstruct their evolution, contribution, artistic, social and political significance, their difficulties and limits. Likewise, to analyze the continuities and discontinuities in their ways of production, organization and creation, in the transition from one historical era to another, that is, before and after the emergence of the unipolar world. Based on this analysis, a reflection on the current situation of independent Latin American theater is proposed.

El teatro independiente en América Latina tuvo su génesis en 1930 cuando Leónidas Barletta fundó en la ciudad de Buenos Aires El Teatro del Pueblo, un proyecto caracterizado por su dimensión social, ética y política inauguradora de un movimiento que desde la capital porteña se extendió poco a poco hacia el resto de América Latina buscando desafiar el statu quo teatral, tanto comercial como oficial, para dar cabida a un teatro moderno y popular. Luego en las décadas de los sesenta y setenta, ya como fenómeno continental, el movimiento independiente trascendió como el más importante espacio de experimentación escénica y de renovación de lenguajes y poéticas teatrales, guiado por una vocación emancipadora de tono social y político que adoptó la colectividad como forma de organización y de creación, y principalmente, donde se buscó forjar una identidad teatral latinoamericana. El objetivo principal de la presente investigación ha sido examinar dicho movimiento a través de tres agrupaciones: El Galpón del Uruguay, La Candelaria de Colombia y Yuyachkani del Perú para reconstruir su devenir, aporte, trascendencia artística, social y política, sus dificultades y límites. Asimismo, para analizar las continuidades y discontinuidades en sus formas de producción, organización y creación en el tránsito de una época histórica a otra, esto es, antes y después de la emergencia del mundo unipolar. A partir de dicho análisis se propone una reflexión sobre la situación que actualmente guarda el teatro independiente latinoamericano.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Doctorado en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-D-2022-1033; Teatro popular; Creación colectiva; Políticas culturales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8350